Hubungan Antara Konsep Diri Dengan Kepercayaan Diri Pada Mahasiswa/I Stambuk 2019 Universitas Medan Area - Mar’i Ahmad Madhy; Annawati Dewi Purba; Nafeesa Nafeesa (Universitas Medan Area, 2022)
This research aims to find out the relationship between self-concept and self-awareness at the time of concentration in front of the class at the Students Faculty of Psychology Class of 2019 at the University of Medan Area. This study was as many as 30 Students. Sampling techniques using purposive sampling. Data collection uses two scales, namely the self-concept scale and self-confidence. Data analysis using pearson product moment correlation technique with rxy = 0.573 with significant p = 0.003 0.05. This means that there is a positive relationship between self-concept and self-confidence assuming that the better the self-concept, the higher the level of self- confidence. On the contrary, the worse the self-concept, the lower the level of self- confidence. Thus, the proposed hypothesis is accepted. The effective contribution of self-concept in self-confidence was 32.8% and the remaining 67.2% was influenced by other factors.